Search of the radio emission from flare stars at decameter wavelengths - Boiko, A.I.; Konovalenko, A.A.; Koliadin, V.L.; Melnik, V.N. (Advances in Astronomy and Space Physics, 2012)
Observations of the two M-dwarf flare stars (AD Leonis and EV Lacertae), which were carried out with the radio telescope UTR-2 (Kharkiv, Ukraine) in the range of 16.5 − 33 MHz, are presented. 167 events of radio emission from AD Leo and 73 events from EV Lac were detected in the period of 2010-2011. These events were considered as stellar emission in ON-OFF regime of observations. The morphology of the probable events in the form of bursts from flare stars is considered and frequency drift rates, durations and uxes of the bursts are analysed.